Thai E-sarn dance on balance and muscle strength in elderly women with falls risk - Chompoopan, Warangkana; Chompoopan, Worawut; Seedaket, Saowaluk; Chotklang, Duangruedee; Pongjan, Siratorn; Kombusadee, Tivapron (International Journal of Public Health Science (IJPHS), 2025)
The risk of falls, which is a significant contributor to mortality among the elderly population, is increasing due to declining balance and muscle strength. A quasi-experimental design was used in this study to examine the effects of traditional Thai E-sarn on balance and muscle strength in older women living in the community. The experimental or control group consisted of 35 people. The experimental group participated in a 12-week fitness regimen utilizing Thai E-sarn. The control group avoided participating in any type of physical activity. The experimental group exhibited notable enhancements in their balance, muscle strength, and health parameters as compared to the control group. In the experimental group, the timed up and go test (TUG) score was reduced by 1.91 seconds (95%CI: 0.67 to 3.16), p=0.003, while the 30-second chair stand test (30CST) increased by 3.15 (95%CI: 1.24 to 5.04), p<0.002. Systolic blood pressure dropped by 6.58 mmHg, diastolic by 5.57, and heart rate by 5.29 beats per minute. These findings suggest regular Thai E-sarn dance may improve balance, muscle strength, and all other parameters. Additional investigation is required to elucidate the impact of exercise on enhancing the general health of older adults.